(untitled) (East West Medical College Journal, 2026)
Background with objective: The ground water is the main source of drinking water in Bangladesh which is already contaminated with high concentration of arsenic. Long-term consumption of such water leads to the development of arsenicosis. Melanosis and keratosis of varying degree are the skin manifestation of arsenicosis. Keratosis is usually noticed on the palm of the hands and sole of the feet. The aim of the present study was to observe the keratosis patients due to arsenicosis. Methodology: This Observational study was carried out among 34 arsenic induced keratosis patients at the Pharmacology department, Bangladesh Medical University (BMU), Dhaka and arsenic affected endemic area Kamalla Union of Muradnagar Upazilla, Cumilla District, Bangladesh from from September 2017 to January 2019. Purposive sampling was done according to availability of the patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: The mean (± SD) age of the patients was 37.3 ± 5.6 years. The mean amount of arsenic was 146.5 ± 82.0 (µg/L) in the tube well water consumed by the patients and Concentration of arsenic in finger nail was 7.5±0.7 µg/g. The mean duration of exposure to arsenic contaminated water of the patients was 8.1 ± 2.0 years. The mean duration of the appearance of keratosis was 6.4 ± 2.2years. The mean size of keratosis nodule was 16.6 ± 5.0 mm2. Most of the patients (n=28, 82.35%) were exposed to arsenic for about six to ten years and 4 patients (11.76%) were exposed to arsenic for about 11 to 15 years. Most of the patients (n=17, 50%) had keratotic nodules for about seven to ten years. Twelve patients (35.29%) had keratotic nodules for about four to six years. In patients with arsenical keratosis, the amount of arsenic in water was within 101- 200 µg/ L in 20 patients, 201 - 300 µg/ L in five patients, 0 – 100 µg/ L in eight patients and 301 – 400 µg/ L in remaining one patient. Conclusion: Patients with chronic arsenicism should have regular long-term examinations because it can cause both cutaneous and systemic neoplasms. EWMCJ Vol. 14, No. 2, July 2026: 179-182